Effect of Fin Geometry on Natural Convection in a Rotated Rectangular Enclosure - Mohaddes Deylami, Hamed (Mechanical Technology and Engineering Insights, 2025)
The natural convection in enclosures is a significant issue in thermal engineering, and internal fins are widely used to improve heat transfer. This current investigation focuses on a numerical investigation of the effects of fin geometry on natural convection heat transfer in a rotated rectangular enclosure. Both square and triangular fins are considered in this investigation, and their effects on fluid flow, temperature distribution, and heat transfer are presented. Numerical simulation of the problem is performed using the finite element method in COMSOL Multiphysics. The numerical simulation is validated with benchmark solutions, and excellent agreement is found. It is found from this investigation that with an increase in Rayleigh number, the effects of buoyancy force on fluid flow and heat transfer increase for both fins. It is found that triangular fins have significant effects on fluid flow and heat transfer compared to square fins. Also, with an increase in fin length, heat transfer increases for low Rayleigh numbers, whereas excessive length of fins reduces heat transfer for high Rayleigh numbers due to blockage of fluid flow. It is found that triangular fins with moderate lengths provide better heat transfer compared to square fins.